Geometric segmentation of 3D scanned surfaces. (May 2015) - Di Angelo, Luca; Di Stefano, Paolo
Abstract: The geometric segmentation of a discrete geometric model obtained by the scanning of real objects is affected by various problems that make the segmentation difficult to perform without uncertainties. Certain factors, such as point location noise (coming from the acquisition process) and the coarse representation of continuous surfaces due to triangular approximations, introduce ambiguity into the recognition process of the geometric shape. To overcome these problems, a new method for geometric point identification and surface segmentation is proposed. The point classification is based on a fuzzy parameterization using three shape indexes: the smoothness indicator, shape index and flatness index . A total of 11 fuzzy domain intervals have been identified and comprise sharp edges, defective zones and 10 different types of regular points. For each point of the discrete surface, the related membership functions are dynamically evaluated to be adapted to consider, point by point, those properties of the geometric model that affects uncertainty in point type attribution. The methodology has been verified in many test cases designed to represent critical conditions for any method in geometric recognition and has been compared with one of the most robust methods described in the related literature. Highlights: A new method to segment geometric features in discrete geometric models is proposed. Sharp edges, defective zones and 10 different types of regular points are recognized. The method requires just a few setting parameters that are not critical. It works with real scanned geometries, highly noised and not well-sampled models. The point type association is not affected by the singular properties of the point.